A new learning environment: designing an urban school dedicated to the learner and the community at large - Rossouw, Renee Elizabeth (School of Architecture, Planning and Geomatics, 2017)
My project is the design of a primary school in an urban context with an interest in developing a school that speaks about new type of learning environments. This typology will address the challenges of designing a school in an urban context, Cape Town, while rethinking how schools are designed with regards to its programme and layout. I am concerned with designing a school which will truly be a space for the learner. This environment is a space where he/she can work/learn together as a group or individually, in classes or in self-study-activities. This environment is a place where the learner can meet and play in an ungoverned manner, where the school building has an equal emphasis on learning and playing. The design of this building should address the needs of the learner as a child that needs to learn, express, move, run. At the same time, the school-building is no longer a sole institution used only by its learners. Rather, it becomes a building which can bring together learners from different schools, and other members of the public to become an active community building. This document will reveal the process of uncovering that Circulation-space is one of the primary spatial components in new School Design - This component will resolve my above-mentioned inquiries as it becomes the solution to architecturally resolving it. This document is divided into the following processes: Chapter l (The Design Principles): I will investigate 3 case studies of three different types of schools and conclude with design principle which will act as design informants for the school I will design. The primary conclusions will then be developed into conceptual ideas whose architectural expression will be addressed in chapter 4. In Chapter 2 (Site Selection), I start of by investigating 6 schools and their facility deficiencies located in close proximity to each other in the city of Cape Town. These deficiencies act as informants to what the Semi-public Shared facilities will be as part of the programme of my school. This chapter also includes diagrams and investigation into the site I have chosen. In Chapter 3 (Timber as Material) I look at different used of timber as a material in school design. Chapter 4 (Design Development), I focus my-design as responding to the challenges of an urban school, as well as further developing the concept of Circulation as one of the primary spatial components in School design. The rest of the chapter will include the spatial explorations of designing the new type of urban school.